Human mesenchymal stromal cells improve scar thickness without enhancing cardiac function in a chronic ischaemic heart failure model - Dayan, Victor (2012)
Few data address the role of human mesenchymal stromal cells (MSCs) in the management of chronic ischaemic heart failure. We assessed their effect in immune-deficient animals. MSCs were cultured from bone marrow of human volunteers. Non-obese diabetes severe combined immunodeficiency (NOD/SCID) gamma null mice were randomly assigned to intramyocardial injection of human MSCs or phosphate-buffered saline 4 weeks after induction of acute myocardial infarction (MI). Echocardiography was performed 4 weeks after MI and 1 and 4 weeks after injection. Donor cell chimerism was assessed by DNA for human Alu sequences 2 and 4 weeks after injection. Histological assessment and quantification of neovascularization were determined 4 weeks after treatment. Donor MSCs at frequencies of 0.006 and 0.001% were present 2 and 4 weeks after cell injection, respectively. The infarcted ventricular wall was significantly thicker in the cohort receiving MSCs compared with control mice. There was no difference in fractional shortening, left ventricular dimensions or scar area between the groups. Small vessel density was also similar between the groups. Human MSCs increased the thickness of the infarcted ventricular wall without improving cardiac function in this chronic ischaemic heart failure model. Further studies are required to assess the benefit of MSCs in this setting.